Use of pornography by young adults in Ireland - Nolan, Anne,Smyth, Emer (The Economic and Social Research Institute, 2024)
This report draws on the Growing Up in Ireland (GUI) study to look at pornography use among over 4,500 young adults at 20 years of age. Pornography use was captured as part of a module of questions on different types of internet use. The rich information provided by the GUI study allows us to explore the potential influence of a range of factors on pornography use and to examine the way use is related to key aspects of wellbeing and sexual behaviour among young adults. Pornography use is found to be highly gendered, with 64 per cent of young men and 13 per cent of young women reporting use. For this reason, analyses in the report look separately at the factors for young women and men.
10.26504/rs177
Keywords: Graue Literatur; Sexualität; Prostitution; Internetnutzung; Junge Erwachsene; Irland